THE EFFECT OF PROVIDING DIFFERENT CONCENTRATE TYPES ON THE PERFORMANCE OF BALI COW THAT PROVIDED WITH FIELD GRASS FEED - M. H. H., Faza; Partama, I. B. G.; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the effect of concentrate on the performance of Bali cows given field-based feed. This research was conducted at the Amerta Sari Farmers Group (KTT), Kesiut Tabanan Village with a randomized block design (RAK). Treatment A was bali cattle given grass which was given ad libitum field plus concentrate containing pollard, treatment B was given ad libitum field grass plus concentrate containing rice bran, treatment C was given ad libitum field grass. The variables observed included ration consumption, daily weight gain, final weight and feed conversion ratio (FCR). The results showed that the NURSING treatment Rations and daily weight gain were above the treatment, namely 5.35 Kg BK / head / day and 0.63 Kg / head / day. The treatment also manages the highest ration management which is calculated with the lowest FCR value of 8.71. Based on the results of this study it can be denied that providing field grass-based rations with the addition of concentrate containing rice bran gives Bali cattle better performance than other treatments. Keywords : bali cattle, concentrate, field grass